Evaluation of niger (Guizotia abyssinica) germplasm for seed yield and its attributes: Evaluation of niger (Guizotia abyssinica) germplasm for seed yield and its attributes - SUVARNA; SHIVALEELA; P H KUCHNUR; J M NIDAGUNDI; B V TEMBHURNE; SANGEETA I MACHA (Journal of Oilseeds Research, 2023)
A total of 114 germplasm of niger along with two check varieties RCR 18 and DNS 4 were evaluated during kharif, 2020 at College of Agriculture, Raichur for seed yield and its attributing characters. The seed yield ranged from 0.7 to 9.0 g/line with a mean of 2.14g. Among all, five genotypes were performed better for seed yield (g) /line viz., IGP-GP-22 (9.0g), ICNR 04 (8.7g), IGP-GP-48 (8.5g), ICNR 05 (8.5g) and DNS 17 (8.4g). Two genotypes ICNR 04 (30 days) and DNS 17 (40 days) exhibited early days to 50% flowering compared to rest of the genotypes.